Avaliação dos aspectos clínicos, moleculares e epidemiológicos da Chikungunya na população do Estado do Maranhão. - SANTOS, Eduardo Mendes dos (2021)
Arboviruses comprise a group of viral diseases transmitted to humans through the bite of infected female arthropods. Arboviruses have a wide geographic distribution, being present in almost all the continents of the globe and are considered a serious public health problem, being responsible for causing outbreaks and epidemics in the world. The main arboviruses that affect human health and other vertebrate animals, such as primates, are members of five families: Bunyaviridae, Flaviviridae, Togaviridae, Reoviridae and Rhabdovidae. Chikungunya, Dengue and Zika viruses are considered endemic in Brazil, causing a high incidence rate every year. This is due to the lack of control of the main mosquito that transmits these viruses, the Aedes Aegypti mosquito, by the population and government actions. In this perspective, this study aims to characterize the sociodemographic and clinical aspects of Chikungunya in the population of the state of Maranhão. Sociodemographic and clinical data were obtained by applying a questionnaire to 179 patients treated at health units in the cities of São José de Ribamar, Paço do Lumiar, Raposa, Santa Inês and Vargem Grande. From 2019 to 2020, Maranhão registered 706 probable cases of chikungunya, and in 2020 there was a reduction of 74.8% of cases compared to 2019. Of the 179 samples, only 3 were positive for Chikungunya. Fever and myalgia were the symptoms most reported by the participants and plasma cholinesterase activity did not show significant results for the identification of arboviruses, however, due to the size of our sample and more robust data, we emphasize that it is necessary to continue with this hypothesis since data reflect positively on the measurement of plasma cholinesterase in patients affected by Covid. However, it is necessary to continue studying the behavior of these arboviruses in our population, especially with the advent of new outbreaks, not only of dengue, zika and chikungunya, but also of covid and flu.